Pengaruh Goal Orientation, Tekanan Anggaran Waktu, Tekanan Ketaatan, Senioritas Auditor Terhadap Audit Judgement: Studi Empiris pada Kantor Akuntan Publik di Provinsi Bali - Kadek Sarmini Agustin; Ni Putu Ayu Kusumawati; I Wayan Budi Satriya (Hita Akuntansi dan Keuangan, 2026)
Audit judgment plays a crucial role in the auditing process, as auditors frequently encounter situations that demand professionalism in addressing risks and materiality in financial statements. The main objective and research question of the present study are in this study, the  aim is to examine the influence of goal orientation, time presssure, compliance pressure, ands auditor seniority on audit judgment. This study was undertaken at public agencies accounting firms in Bali Province, involving a sample of 63 respondents. The study applies several analytical techniques multiple linear regression. hes research findings reveal that purpose orientastion has a possitive and signifficant effect on audit judgment, time pressuree has a negative and signifficant effect on audit judgment, compliance pressure has a negative and signifficant effect on audit judgment, and auditor seniority has a positive and significant effect on audit judgment. The independent variables collectively explain 76.1% of the variation in audit judgment.